Peso en cuyes en etapa reproductiva con una segunda progenie de cruce genético de tipo absorbente - Chimbo López, Jessenia Carolina (2017)
This research is based on guinea pigs production enhancement in accordance with the following goals: To determine the weight gain in the guinea pigs in their reproductive stage with a second progeny of genetic cross with an absorbent type at CEYPSA, verify the guinea pigs characteristics in the first progeny through the genetic selection parameters in the reproductive stage in order, amelioration evaluate the best animals in the first progeny in relation to their characteristics of weight gain in their reproductive stage to establish genetic improvement, relate the weight gain of guinea pigs in their reproductive stage of the first and second progeny though a comparative analysis in order to value the accomplished gripping cross. For management 77 animals were categorized according colors of coats, absence or presence of a swirl in their head, its identification was done by metal earrings, getting the following results: The category with the best weight gain in the second progeny was the number 3 (painted with wirl) with 32,51 gr, then category 6 (White) with a medium weight gain of 30,24 gr, after the category number 2 (Red with wirl) with 11,14 gr, then the category number 1 (Red without wirl) with their weight -3,72 gr, finally the category number 5 (Guinea pigs) their weight was -6,66 gr. The negative weight is related to an improper handing on the forage cross provisioning. Therefore it is concluded the best weight gain was the painted guinea pigs with swirl and white, they were selected as the most suitable categories to gain weight. According the Pearson correlation (r=0, 21) determined the same one is weak because it is close to 0, It should be noted that there is no relation between the first and second progeny.